Creatine supplementation enhances anti-tumor immunity by promoting adenosine triphosphate production in macrophages - Peng, Zhenzi; Saito, Suguru (Frontiers in Immunology, 2023)
Creatine is an indispensable organic compound utilized in physiological environments; however, its role in immunity is still poorly understood. Here, we show that creatine supplementation enhances anti-tumor immunity through the functional upregulation of macrophages by increasing adenosine triphosphate (ATP) production. Creatine supplementation significantly suppressed B16-F10-originated tumor growth in mice compared to the control treatment. Under these conditions, intratumor macrophages polarized towards the M1 phenotype rather than the M2 phenotype, and there was an increase in tumor antigen-specific CD8+ T cells in the mice. The cytokine production and antigen-presenting activity in the macrophages were enhanced by creatine supplementation, resulting in a substantial increase in tumor antigen-specific CD8+ T cells. ATP upregulation was achieved through the cytosolic phosphocreatine (PCr) system via extracellular creatine uptake, rather than through glycolysis and mitochondrial oxidative phosphorylation in the macrophages. Blockade of the creatine transporter (CrT) failed to upregulate ATP and enhance the immunological activity of macrophages in creatine supplementation, which also impaired CD8+ T cell activity. Consequently, CrT blockade failed to suppress tumor growth in the creatine-supplemented mice. Thus, creatine is an important nutrient that promotes macrophage function by increasing ATP levels, ultimately contributing to enhanced anti-tumor immunity orchestrated by CD8+ T cells.